Optimizing The Role Of The Community Against Drug Abuse as a Form Of Countermeasure In Realizing a Clean Village From Drugs - Qothrun Nada Zahrotun Nabila; Amalia Farihal Husna; Rio Taqy Fadillah; Ashwa Cinta; Maulana Arie Saputra; Kartika Ning Tyas; Widi Cahya Adi (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The rise of drug trafficking in Indonesia based on the results of BNN data processing still shows a high crime rate, which in the last 2023 reached 4,244,267 people exposed to drugs. Of course, drug crime is a problem that must be strictly prevented and supervised, because gen z is one of the targets of this crime. This is very necessary to be aware of, considering that gen z is the hope of the nation which will be able to advance, develop and educate the nation. The implementation and participation of the role of the community that is carried out optimally can be an effective step in trying to tackle drug abuse. Qualitative method is the method used by researchers. Through observation and literature study, it is possible to know factually about the level of understanding and behavior of the community with the holding of socialization supported by books and journals as research sources. This study aims to determine the role of the community against drug abuse in realizing a clean village from drugs.